Microlearning: in Media Social TikTok Video - Meliana, Rizka; Seli, Fenny Yutika (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This study explores the potential of utilizing social media, particularly TikTok, as an effective educational tool for enhancing English as a Foreign Language (EFL) learning. Employing a descriptive qualitative research method, the study conducted a content analysis of 100 TikTok videos, categorizing them into productive (speaking and reading) and receptive (listening and writing) skills. The research findings indicate that microlearning, represented by short and interactive content, can be a successful approach for delivering language learning materials through TikTok videos. By integrating innovative approaches like microlearning and leveraging the popularity of social media platforms, educators can create engaging and interactive learning experiences for EFL learners, fostering collaborative learning and academic connections